Diversity and distribution of class insecta from selected area of Tuba Island reserve forest - Siti Khairiyah Mohd Hatta,; Nursyafieza Rusidilbukhari,; Nur Nadiah Md Yusof,; Norashirene Mohamad Jamil,; Kamarul Hambali,; Noor Akmal Abd Wahab,; Siti Noorfahana Mohd Idris,; Norhafizah Mohd Zazi,; Faezah Pardi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Insects are ubiquitous and inhabit all types of ecosystems that include island ecosystems. A study on the diversity and distribution of Class Insecta was conducted at a selected forest area in Pulau Tuba using malaise traps. No insect study has been conducted at Pulau Tuba before. Three study sites namely forest fringe, middle forest, and inner forest were chosen. A total of 5883 specimens belonging to seven orders and 106 morphospecies of insects were collected. The orders identified were Blattodea, Coleoptera, Diptera, Hymenoptera, Hemiptera, Isoptera, and Lepidoptera. Diptera samples were the most found while Blattodea recorded the lowest number recorded. Shannon-Wiener Diversity Index (H’) showed that the inner forest had the highest diversity value with H’ = 0.53, followed by the forest fringe with H’ = 0.44, and the middle forest with H’ = 0.22. The Evenness Index (E’) and Margalef Richness Index (R’) also showed the highest value comes from the inner forest with E’ = 0.28 and R’ = 0.81 respectively. Kruskal-Wallis test showed that there was a significant difference in insect distribution across three study sites where P< 0.05. Overall, this study suggested that the diversity of Class Insecta at Pulau Tuba was low in the three locations confirming the low species richness of insects in the island forest ecosystem.